2015
DOI: 10.1177/194849921500600005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pitch and Rhythm Difficulty on High School String Sight-Reading Performance

Abstract: Reading music at sight is a complex skill, requiring the musician to perform pitch and rhythm simultaneously. Previous research has identified difficulty levels for pitch and rhythm skills for strings individually but not in combination. In this study, we sought to study possible relationships between pitch and rhythm tasks occurring concurrently. High school string players (N = 88) performed melodies with varying combinations of pitch and rhythm difficulty. Results indicated that pitch and rhythm skills retai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Treatments in this study were designed to isolate the roles of rhythm and pitch in music reading. Investigators have observed an interaction between pitch accuracy and timing accuracy (Alexander & Henry, 2015; Cassidy et al., 2001; Henry, 2011; Pike & Carter, 2010). Building on those observations, I asked what the effects would be on the accuracy of performing music from notation if participants were primed with rhythm or pitch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatments in this study were designed to isolate the roles of rhythm and pitch in music reading. Investigators have observed an interaction between pitch accuracy and timing accuracy (Alexander & Henry, 2015; Cassidy et al., 2001; Henry, 2011; Pike & Carter, 2010). Building on those observations, I asked what the effects would be on the accuracy of performing music from notation if participants were primed with rhythm or pitch.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that factors other than knowing how the rhythm goes may be more important to a fluent performance. It has been observed in singers and string playing that students first attend to the pitch (what to play) and then timing (when to play) during sight-reading (Alexander & Henry, 2015; Henry, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation